Antioxidant Activity of Mangrove Sonneratia caseolaris L using the FRAP Method - Raharjo, Danang; Haryoto, H (Universitas Muhammadiyah Surakarta, 2019)
Antioxidants are compounds that have an important role in maintaining health because they can ward off free radicals that inhibit oxidation reactions in the body that cause various diseases. Antioxidant compounds are many flavonoid compounds found in mangrove plants. The purpose of this study was to determine the antioxidant activity of red pidada leaves (Sonneratia caseolaris L) using the Ferric Reduction Antioxidant Power (FRAP) method with vitamin C as a comparison. The research process begins with the extraction of red pidada (Sonneratia caseolaris L) leaves with ethanol. The extraction process was carried out by maceration method for 3 x 24 hours @ 24 hours and continued with fractionation. The maserate obtained was then evaporated with a rotary evaporator at a temperature of 40 - 60OC obtained a thick extract, then the fractions obtained were non-polar, semi-polar and polar fractions. The results showed antioxidant activity; ethanol extract, non-polar, semi-polar and polar fractions were 6.37; 5,35; 6.59 and 5.96 mgAAE / g.